⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ a + b + c = 5 a 2 + b 2 + c 2 = 8 3 a 3 + b 3 + c 3 = 2 4 5 a 4 + b 4 + c 4 = 3 1 0 7
Let a , b and c be integers satisfying the system of equations above. Find the value of a 5 + b 5 + c 5 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I found the answer by solving for a in equation 1 and substituting into the second and third equations. I was left with abc = -105. Assuming the variables were integers, I thought about the possible factors of 105. There are three prime factors of 105: 3, 5, and 7. One has to be negative. Obviously, 5 is negative because the three added together must equal 5 and 3 + 7 - 5 = 5. Raising them all to the fifth power yields: 243 + 16807 - 3125 = 13925
In detail,
a = 5 − b − c = 5 − ( b + c ) a 2 = 2 5 − 1 0 ( b + c ) + ( b + c ) 2 a 3 = 1 2 5 − 7 5 ( b + c ) + 1 5 ( b + c ) 2 − ( b + c ) 3
Substitute into the second equation: a 2 + b 2 + c 2 = 2 5 − 1 0 ( b + c ) + ( b + c ) 2 + b 2 + c 2 = 2 5 − 1 0 b − 1 0 c + b 2 + 2 b c + c 2 + b 2 + c 2 = 2 5 − 1 0 b − 1 0 c + 2 b 2 + 2 b c + 2 c 2 = 8 3
Subtract 25 from both sides and divide both sides by 2: 2 9 = − 5 b − 5 c + b 2 + b c + c 2
Substitute into third equation: 1 2 5 − 7 5 ( b + c ) + 1 5 ( b + c ) 2 − ( b + c ) 3 + b 4 + c 4 = 1 2 5 − 7 5 b − 7 5 c + 1 5 b 2 + 3 0 b c + c 2 − b 3 − 3 b ( 2 ) c − 3 b c 2 − c 3 + b 3 + c 3 = 1 2 5 − 7 5 b − 7 5 c + 1 5 b 2 + 3 0 b c + 1 5 c 2 − 3 b 2 c − 3 b c 2 = 2 4 5
Subtracting 125 and dividing by 3 yields: − 2 5 b − 2 5 c + 5 b 2 + 1 0 b c + 5 c 2 − b 2 c − b c 2 = 4 0
Split 10bc into 5bc + 5bc and rearrange like so: − 2 5 b − 2 5 c + 5 b 2 + 5 b c + 5 c 2 + 5 b c − b 2 c − b c 2 = 4 0
Factor 5 out of the first five terms: 5 ( − 5 b − 5 c + b 2 + b c + c 2 ) + 5 b c − b 2 c − b c 2 = 4 0
The expression in parentheses is one side of our new equation 2. It's equal to 29. 5 ( 2 9 ) + 5 b c − b 2 c − b c 2 = 4 0 1 4 5 + 5 b c − b 2 c − b c 2 = 4 0 5 b c − b 2 c − b c 2 = − 1 0 5 b c ( 5 − b − c ) = − 1 0 5 a b c = − 1 0 5 = 3 ∗ 7 ∗ ( − 5 )
To check: 3 + 7 − 5 = 5 9 + 4 9 + 2 5 = 8 3 2 7 + 3 4 3 − 1 2 5 = 2 4 5 8 1 + 2 4 0 1 + 6 2 5 = 3 1 0 7
And the final answer is: 2 4 3 + 1 6 8 0 7 − 3 1 2 5 = 1 3 9 2 5
Problem Loading...
Note Loading...
Set Loading...
Newton's Sums tell us that in a polynomial f ( x ) of n degrees with coefficients a n , a n − 1 , a n − 2 , … , a 0 such that 0 = a n x n + a n − 1 x n − 1 + a n − 2 x n − 2 + … + a 1 x + a 0 , the sums of the roots x 1 , x 2 , x 3 , … of the polynomial raised to powers can be represented in terms of the coefficients in a system of equations:
a n P ( 1 ) + 1 a n − 1 = 0 a n P ( 2 ) + a n − 1 P ( 1 ) + 2 a n − 2 = 0 a n P ( 3 ) + a n − 1 P ( 2 ) + a n − 2 P ( 1 ) + 3 a n − 3 = 0 a n P ( 4 ) + a n − 1 P ( 3 ) + a n − 2 P ( 2 ) + a n − 3 P ( 1 ) + 4 a n − 4 = 0 a n P ( 5 ) + a n − 1 P ( 4 ) + a n − 2 P ( 3 ) + a n − 3 P ( 2 ) + a n − 4 P ( 1 ) + 5 a n − 5 = 0 a n P ( 6 ) + … = 0
and so on and so forth.
If we imagine a , b and c as the roots of a 3 rd degree polynomial, then we can apply Newton's Sums to find P ( 5 ) = a 5 + b 5 + c 5 .
Start by defining some variables... we will solve for the other coefficients in terms of the leading coefficient and then find P ( 5 ) .
P ( 1 ) = a + b + c = 5 P ( 2 ) = a 2 + b 2 + c 2 = 8 3 P ( 3 ) = 2 4 5 P ( 4 ) = 3 1 0 7 P ( 5 ) = unknown and what we are looking for! a n = x a n − 1 = y a n − 2 = z a n − 3 = p a n − 4 = 0 a n − 5 = 0
a n P ( 1 ) + 1 a n − 1 = 0 ⇒ 5 x + y = 0 ⇒ y = − 5 x
a n P ( 2 ) + a n − 1 P ( 1 ) + 2 a n − 2 = 0 ⇒ 8 3 x + 5 y + 2 z = 0 ⇒ 5 8 x + 2 z = 0 ⇒ z = − 2 9 x
a n P ( 3 ) + a n − 1 P ( 2 ) + a n − 2 P ( 1 ) + 3 a n − 3 = 0 ⇒ 2 4 5 x + 8 3 y + 5 z + 3 p = 0 ⇒ − 3 1 5 x + 3 p = 0 ⇒ p = 1 0 5 x
All coefficients after p are 0 because our Newton's Sums are for a 3 rd degree polynomial with only four coefficients, so now we can skip straight to finding P ( 5 )
⇒ a n P ( 5 ) + a n − 1 P ( 4 ) + a n − 2 P ( 3 ) + a n − 3 P ( 2 ) + a n − 4 P ( 1 ) + 5 a n − 5 = 0 ⇒ x ⋅ P ( 5 ) + 3 1 0 7 ( − 5 x ) + 2 4 5 ( − 2 9 x ) + 8 3 ( 1 0 5 x ) + 5 ( 0 ) + 6 ( 0 ) ⇒ x ⋅ P ( 5 ) − 1 3 9 2 5 x = 0 ⟹ a 5 + b 5 + c 5 = 1 3 9 2 5 .
For more information on Newton's Sums, check here: http://www.artofproblemsolving.com/wiki/index.php/Newton's_Sums. This method may look very complicated and time-consuming, but once you understand it, problems like this one take significantly less time than they would otherwise.